Perang Dagang Dan Proteksionisme: Kajian Ekonomi Politik Atas Kebijakan Tarif Dalam Hubungan Dagang Bilateral - Chindy Nurul Fadilah, Enjum Jumhana; Enjum Jumhana; Tasya Salsabilla; Nadya Septiani; Rayhan Zamir; Wafiroh (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Trade wars and protectionism have again become major issues in global economic dynamics, especially since trade tensions between the United States and China began in 2018. This research aims to analyze tariff policy as part of a protectionist strategy in the context of the political economy of bilateral trade relations. Using a qualitative approach with case studies and document analysis, data were obtained from policy reports, scientific journals, and trade statistics. The results show that tariff policies are often not purely based on economic considerations, but are also influenced by domestic political interests, industry group pressure, and global negotiation strategies. On the other hand, these policies have a significant impact on the structure of bilateral trade relations, trade volume, and global supply chains. Indonesia as a partner country is also affected, both directly through changes in export-import values, and indirectly through supply and investment disruptions. Policy implications show the importance of developing countries' preparedness in anticipating changes in global trade policies and encouraging the formulation of adaptive and competitive national strategies. This study provides recommendations for policymakers to balance national interests with global dynamics.